ANALISIS KEBIJAKAN UNTUK PENGELOLAAN MINYAK DAN GAS (STUDY KASUS LAPANGAN “X”) - Ramli Nonci; Akhmad Fauzi; Fifi Diana Thamrin (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2020)
Indonesia is one of the countries in the world that have potential of natural resources such as oil and gas. As a resource, that plays an important role in the economic life, the use of oil and gas needs to be managed properly. One of the resources of oil and gas that have significant production value and impact to the economy of Indonesia is the “X” field at East Kalimantan. This study aims to provide analyze policies that can encourage the management of the remaining oil and gas fields more optimally. Data used in the study came from the results of the discussions, field observations, literature review government policies and company documentation on 2019. The analytical tool used is the multi criteria decision analysis (MCDA) method. Based on the analysis of policies for the development of the "X" field by taking into account economic, social, and HSE (Health, Safety and Environment)  criteria results in a conclusion that Gross Split policy alternative has the highest value compared to the Cost Recovery policy and the Cost and Fee policy for the design of oil and gas management policies.